Individual differences in the influence of task-irrelevant Pavlovian cues on human behavior - Garofalo, Sara; di Pellegrino, Giuseppe (Frontiers in Behavioral Neuroscience, 2015)
Pavlovian-to-instrumental transfer (PIT) refers to the process of a Pavlovian reward-paired cue acquiring incentive motivational proprieties that drive choices. It represents a crucial phenomenon for understanding cue-controlled behavior, and it has both adaptive and maladaptive implications (i.e., drug-taking). In animals, individual differences in the degree to which such cues bias performance have been identified in two types of individuals that exhibit distinct Conditioned Responses during Pavlovian conditioning: Sign-Trackers (ST) and Goal-Trackers (GT). Using an appetitive PIT procedure with a monetary reward, the present study investigated, for the first time, the extent to which such individual differences might affect the influence of reward-paired cues in humans. In a first task, participants learned an instrumental response leading to reward; then, in a second task, a visual Pavlovian cue was associated with the same reward; finally, in a third task, PIT was tested by measuring the preference for the reward-paired instrumental response when the task-irrelevant reward-paired cue was presented, in the absence of the reward itself. In ST individuals, but not in GT individuals, reward-related cues biased behavior, resulting in an increased likelihood to perform the instrumental response independently paired with the same reward when presented with the task-irrelevant reward-paired cue, even if the reward itself was no longer available (i.e., stronger PIT effect). This finding has important implications for developing individualized treatment for maladaptive behaviors, such as addiction.